1990
DOI: 10.1051/apido:19900303
|View full text |Cite
|
Sign up to set email alerts
|

Cornual secretion on the endophallus of the honeybee drone (Apis mellifera L)

Abstract: Summary — The orange cornual layer of the drone's endophallus is produced by gland cells in the epithelium of the comua. The occurrence of its pigment is age-dependent as newly emerged drones have no pigmentation, and all colony drones older than 4 d had orange comua during the reproductive season (May and June). The absorbancy spectrum of the pigments extracted in dioxane has maxima at 300 nm, 380 nm and 500 nm. In extracts from 4-d-old drones, the amount of absorbing substances was less than in extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Specific experimental manipulations would be needed to test the relative importance of internal, external, and social factors for the timing of drone hyperactivity. There is suggestive evidence that internal factors determine flight time in drones; researchers used a flight room to clock-shift drones, and found that when moved outdoors, the drones retained their clock-shifted departure time (Pfannenstiel and Koeniger, 2000). These findings, however, were published as an abstract, and so would need to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Specific experimental manipulations would be needed to test the relative importance of internal, external, and social factors for the timing of drone hyperactivity. There is suggestive evidence that internal factors determine flight time in drones; researchers used a flight room to clock-shift drones, and found that when moved outdoors, the drones retained their clock-shifted departure time (Pfannenstiel and Koeniger, 2000). These findings, however, were published as an abstract, and so would need to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…In all the examined drones, the colour of the cornua was checked. It was assumed that in immature drones the cornua are transparent, whereas in mature drones they are orange (Koeniger et al, 1990). Semen was collected in a calibrated microcapillary from each drone which everted its endophallus.…”
Section: Methodsmentioning
confidence: 99%
“…Starting at three days of age, spermatozoa are transferred to the seminal vesicles and reach their highest number when the drones turn 8 to 12 days old, depending on the studies [ 18 , 60 ]. The secretions of endophallus accessory glands, including mucus and corneal glands, also mature, being fully functional at 9–12 days [ 18 , 61 , 62 ]. Taken together, data on sperm maturation and flight activity both suggest that drones are not fully sexually operational before 10–12 days of age.…”
Section: Introductionmentioning
confidence: 99%